(untitled) (Universal International Scientific Journal, 2026)
In the period of socio-spiritual development of new Uzbekistan, the awareness of the identity of psychologists who ensure the mental health and social stability of the nation has become a pressing issue. National identity is not just a person’s belonging to a particular nation, but a complex phenomenon that determines his perception of the world, professional approaches and value system.